The Concept of “Indirect Expropriation”, its appearance in the international system and its effects in the regulatory activity of governments. (2011)
The protection of an alien s property in a host country against direct expropriation has long existed in the international arena. Examples of direct expropriation include nationalization; physical seizure of assets or legislated transfer of assets to the state. However such physical takings are no longer common practice. Nowadays; expropriation comes mainly in the form of indirect expropriation : acts and steps taken by governments which interfere with the right to the property or diminish the value of the property. This paper explores the most relevant antecedents of the concept of indirect expropriation; its appearance in the international system; the inclusion in BITs and Investment Chapters of FTAs; and the effect that the concept is having on the regulatory activity of governments.